FAKTOR-FAKTOR PENENTU DISIPLIN KERJA YANG DIMEDIASI KOMITMEN ORGANISASI PADA POLDA JATENG - Andi Krisbianto; Endah Winarti HS; Mochammad Taufiq (DHARMA EKONOMI, 2022)
ABSTRACTThe purpose of this study was to analyze the effect of career development and financial compensation on work discipline with organizational commitment as a mediating variable. The population in this study were Semarang Police Academy employees with a total of 849 personnel. The sampling technique used the Slovin formula with an error limit of 5%, 272 respondents were obtained, and 194 data were processed using SPSS. The results of hypothesis testing show that career development has a significant positive effect on organizational commitment. Financial compensation has a significant positive effect on organizational commitment. Organizational commitment has a significant positive effect on work discipline. Career development has a significant positive effect on work discipline. Financial compensation has a significant positive effect on work discipline. The results of the analysis of mediating variables using the Sobel test state that organizational commitment can mediate the influence of career development on work discipline. This proves organizational commitment as a mediating variable from the influence of career development on work discipline. Organizational commitment can mediate the effect of financial compensation on work discipline. This proves organizational commitment as a mediating variable from the effect of financial compensation on work discipline. Keywords: career development, financial compensation, organizational commitment, work discipline ABSTRAKTujuan penelitian ini untuk menganalisis pengaruh pengembangan karier dan kompensasi finansial terhahap Disiplin kerja dengan komitmen organisasi sebagai variabel mediasi. Populasi dalam penelitian ini adalah karyawan Akademi Kepolisian Semarang sebanyak 849 personel. Tehnik pengambilan sampel menggunakan rumus Slovin dengan batas kesalahan 5 % didapat 272 responden, dan data yang diolah sebanyak 194 menggunakan SPSS. Hasil pengujian hipotesis menunjukan pengembangan karier berpengaruh positif signifikan terhadap komitmen organisasi. Kompensasi finansial berpengaruh positif signifikan terhadap komitmen organisasi. Komitmen organisasi berpengaruh positif signifikan terhadap disiplin kerja. Pengembangan karier berpengaruh positif signifikan terhadap disiplin kerja. Kompensasi finansial berpengaruh positif signifikan terhadap disiplin kerja. Hasil analisis variabel mediasi dengan menggunakan uji Sobel, menyatakan komitmen organisasi dapat memediasi pengaruh pengembangan karier terhadap disiplin kerja. Hal ini membuktikan komitmen organisasi sebagai variabel mediasi dari pengaruh pengembangan karier terhadap disiplin kerja. Komitmen organisasi dapat memediasi pengaruh kompensasi finansial terhadap disiplin kerja. Hal ini membuktikan komitmen organisasi sebagai variabel mediasi dari pengaruh kompensasi finansial terhadap disiplin kerja. Kata kunci: pengembangan karier, kompensasi finansial, komitmen organisasi, disiplin kerja